Laboratory diagnosis of heparin-induced thrombocytopenia type II after clearance of platelet factor 4/heparin complex - Harenberg, Job; Wang, Lianchun; Hoffmann, Ursula; Huhle, Günter; Feuring, Martin (The journal of laboratory and clinical medicine, 2001)
Laboratory confirmation of heparin-induced thrombocytopenia (HIT) is limited by assay sensitivity. We investigated whether laboratory confirmation can be improved after antigen clearance by determining free antibody and combining the results of antigenic and biologic assays. Blood samples were collected over 5 to 6 weeks in 14 HIT patients. As an antigenic assay, the fluorescence-linked immunofiltration assay (FLIFA) was performed, and as a biologic assay, the carbon 14-labeled serotonin release assay was performed. At day 1 when heparin was stopped, 11 of 14 patients showed positive results in both assays; thus each assay had a sensitivity of 80%. The 3 patients with negative results seroconverted in one or both assays during the subsequent 7 days. Combining the positive results of the assays increased the sensitivity to 100% at day 7, regardless of whether the antigenic or the biologic assay was performed first. Both assays became negative in all patients within 5 to 6 weeks. The sensitivity of antigen and biologic assays in HIT patients increased to 100% after the time course of the heparin-induced antibody. We assume that in some HIT patients the free antibody can be detected after withdrawal of heparin and after clearance of the platelet-factor 4/heparin complex. (J Lab Clin Med 2001;137:408-13)